2022
DOI: 10.3389/fnmol.2021.827370
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Birth Alters the Maturation of the GABAergic System in the Human Prefrontal Cortex

Abstract: Developmental changes in GABAergic and glutamatergic systems during frontal lobe development have been hypothesized to play a key role in neurodevelopmental disorders seen in children born very preterm or at/with low birth weight, but the associated cellular changes have not yet been identified. Here we studied the molecular development of the GABAergic system specifically in the dorsolateral prefrontal cortex, a region that has been implicated in neurodevelopmental and psychiatric disorders. The maturation st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
(61 reference statements)
1
8
1
Order By: Relevance
“…During adolescence, the brains of our mouse model also showed hypomyelination, a condition observed in preterm newborns ( 1 ) and suggested to be among the causes of several other neurological and behavioral disabilities ( 1 ). Our mouse model similarly reproduced a reduced number of interneurons in the cortex, which is also observed in preterm newborns ( 27 , 51 ) and frequently associated with psychiatric disorders ( 52 ). Furthermore, EEG recordings in awake head-fixed mice (similar to the resting state in humans) uncovered a decreased high-frequency power–to–low-frequency power ratio, previously associated with immature neuronal circuits ( 53 ).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…During adolescence, the brains of our mouse model also showed hypomyelination, a condition observed in preterm newborns ( 1 ) and suggested to be among the causes of several other neurological and behavioral disabilities ( 1 ). Our mouse model similarly reproduced a reduced number of interneurons in the cortex, which is also observed in preterm newborns ( 27 , 51 ) and frequently associated with psychiatric disorders ( 52 ). Furthermore, EEG recordings in awake head-fixed mice (similar to the resting state in humans) uncovered a decreased high-frequency power–to–low-frequency power ratio, previously associated with immature neuronal circuits ( 53 ).…”
Section: Discussionsupporting
confidence: 65%
“…Because preterm newborns nowadays may show long-term brain microstructural alterations, including decreased white matter myelination [a clinical hallmark of preterm brain disorder ( 1 )] and a reduced number of cortical interneurons ( 27 ), we investigated whether interfering with IGF-1 signaling early in development leads to similar alterations in JB1-treated mice when they are adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of structural damage, prematurity seems to selectively affect astrocyte maturation in the prefrontal cortex. As a consequence, PTs may exhibit a lower number of functioning synapses around TEA as compared to their FT peers, potentially explaining their greater hypoperfusion in the Fronto‐Temporal cluster (Lacaille et al, 2021 ). Supporting this interpretation, adult studies reported the presence of thinner cortices in the frontal, temporal, and parietal associative areas of individuals born PT but without overt brain injury (Schmitz‐Koep et al, 2020 ; Zubiaurre‐Elorza et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sex, completed gestational weeks and cause of death varied, but the majority were caused by sudden infant death syndrome, with no CNS infection, hemorrhage or malformation noted. Donors’ information were previously reported in ( 46 ).…”
Section: Methodsmentioning
confidence: 99%